Design practices and principles for promoting dialogic argumentation via interdisciplinarity. (December 2022) - Koichu, Boris; Schwarz, Baruch B.; Heyd-Metzuyanim, Einat; Tabach, Michal; Yarden, Anat
Abstract: Past research has shown various benefits of combining the argumentative and the dialogic in cognitive development. However, it has also shown that attempts to implement dialogic argumentation in school fail to leave a sustainable impact. One reason for this situation is related to the lack of explicit knowledge about how to design and organize dialogical activities in realistic school settings. The present study addresses this lacuna while putting forward interdisciplinarity as a promising venue for promoting student dialogue and argumentation. We first elaborate on the connection between dialogic argumentation and interdisciplinarity, review the relevant literature on instructional and task design and then suggest a configuration of the design principles needed to be developed: these are content-related principles, pedagogy-related principles and organization-related principles. This is followed by an illustration of how specific design principles of these types emerged from and are reflected in task-design practices of project team of researchers in science, mathematics and philosophy education. Finally, we show that while the focus on interdisciplinarity seems to narrow the issue of the implementation of dialogue and argumentation in schools, it in fact opens it and provides instructional design principles in complex educational projects relevant to the society.